Pneumothorax complicating pulmonary embolism after combined spinal epidural anesthesia in a chronic smoker with open femur fracture - Shivendu Bansal; Sohan Lal Solanki; Neena Jain; V K Vijayvergia (Wolters Kluwer Medknow Publications, 2011)
Pulmonary embolism during or after regional anaesthesia is although very rare, it has been reported in cases undergoing lower limb orthopedic procedures. We presenting a 48 years old male, a known smoker since 25 years, with history of road traffic accident and open fracture right femur for external fixation. Combined spinal epidural anaesthesia was given. After 35 minutes patient complained dyspnea and chest pain. SpO2 decreased to 82% from 100%. Continuous positive airway pressure with 100% oxygen was given. SpO2 increased from 82% to 96%. Suddenly he had bouts of cough and SpO2 became 79-80% with unstable haemodynamics. On chest auscultation there was decreased breath sounds on right side with limited expansion. Trachea was intubated after inducing anaesthesia with fentanyl 70 μg and thiopental 300 mg. Chest radiograph showed right sided pneumothorax. Intercostal drain with a water seal was put. After 5 minutes HR was 80/min, BP was 110/69 mmHg and SpO2 was 97%. Pulmonary thromboembolism secondary to deep vein thrombosis was suspected and was confirmed by D-dimer Elisa and color Doppler of lower limbs. Patient was shifted to intensive care unit after completion of surgery. Anticoagulant therapy was started. He was weaned from the ventilator on 3rd day and trachea was extubated. Chest drain was removed after 9 days and he was discharged from hospital on 15th post operative day